2020
DOI: 10.1111/jrh.12530
|View full text |Cite
|
Sign up to set email alerts
|

Rural Primary Care Providers’ Experience and Usage of Clinical Recommendations in the CDC Pediatric Mild Traumatic Brain Injury Guideline: A Qualitative Study

Abstract: Purpose In 2018, the Centers for Disease Control and Prevention (CDC) released an evidence‐based guideline on pediatric mild traumatic brain injury (mTBI) to educate health care providers on best practices of mTBI diagnosis, prognosis, and management/treatment. As residents living in rural areas have higher rates of mTBI, and may have limited access to care, it is particularly important to disseminate the CDC guideline to rural health care providers. The purpose of this paper is to describe rural health care p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“… PCPs often did not document important aspects of concussion history or physical examination. Retrospective chart review Daughery et al 23 2021 Rural health care providers No intervention was completed. Health care providers found CDC guideline recommendations to be helpful and feasible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… PCPs often did not document important aspects of concussion history or physical examination. Retrospective chart review Daughery et al 23 2021 Rural health care providers No intervention was completed. Health care providers found CDC guideline recommendations to be helpful and feasible.…”
Section: Resultsmentioning
confidence: 99%
“…A qualitative study by Daugherty et al 23 described the opinion of PCPs in rural communities on the Centers for Disease Control and Prevention's evidence-based guidelines on pediatric mTBI. PCPs were concerned that the Centers for Disease Control and Prevention guidelines were lengthy and nonspecific to rural communities.…”
Section: Resultsmentioning
confidence: 99%
“…The current update examines important trends in healthcare utilization, provider practices and perceptions, and gaps in care and implementation across EDs, primary care, and school-based settings across two large retrospective studies and three focused survey studies in the US and Canada [29][30][31][32][33].…”
Section: Care Practicesmentioning
confidence: 99%
“…Care can differ by practice location. Primary and acute care clinicians care for the majority of concussions in youth, with studies reporting gaps in knowledge, lack of use of established guidelines, challenges with specialist access, and perceived limited training for such providers 13–15. Ultimately, varied care can lead to sociodemographic disparities related to pediatric concussion care.…”
mentioning
confidence: 99%
“…Primary and acute care clinicians care for the majority of concussions in youth, with studies reporting gaps in knowledge, lack of use of established guidelines, challenges with specialist access, and perceived limited training for such providers. [13][14][15] Ultimately, varied care can lead to sociodemographic disparities related to pediatric concussion care. Specifically, previous studies have found racial disparities in concussion symptom recognition, 16 reporting of concussions, 17 and utilization of the emergency department (ED) for concussion.…”
mentioning
confidence: 99%